The impact of continuous and intermittent supportive counseling on self-efficacy and continuation of breastfeeding in lactating women affected by COVID-19: a quasi-experimental trial - Maryam Karimi; Azam Maleki; Leila Rastegari (BMC, 2024)
Abstract Background Promoting exclusive breastfeeding can have a great effect in reducing the complications and mortality rate of mother and child. Objective The study aimed to compare the effects of continuous and intermittent supportive counselling on the self-efficacy and continuity of breastfeeding among Lactating mothers with COVID-19. Methods The study was a semi-experimental research method and was conducted on 73 mothers with COVID-19 who were hospitalized in Ayatollah Mousavi Hospital in Zanjan, Iran from May 2021 to April 2022. In the continuous counselling group, counselling was provided daily for 14 days, while in the intermittent counselling group, counselling was provided once a week for four weeks. Breastfeeding continuity was assessed based on the World Health Organization's classification, and breastfeeding self-efficacy was measured using Dennis' standard breastfeeding self-efficacy questionnaire (BSE) up to four months after delivery. The data were analyzed using chi-square tests, independent t-tests, paired t-tests, analysis of variance with repeated measures, and survival analysis (Kaplan-Meier) with a 95% confidence level. Results The survival analysis revealed that the cessation of exclusive breastfeeding occurred in 17 cases within the continuous counselling group and in 22 cases within the intermittent counselling group. The rates of continuation for exclusive breastfeeding were 52.8% and 40.5% in the continuous and intermittent counselling group respectively. However, no statistically significant differences were observed in the continuation of breastfeeding and the trend of changes in the mean scores of breastfeeding self-efficacies between the continuous and intermittent counselling groups. Furthermore, comparing the change in breastfeeding self-efficacy scores between the one-month and four-month follow-ups within the continuous counselling group, a statistically significant increase was observed. Conclusion The results indicated no difference in the effectiveness of continuous and intermittent counseling methods in improving breastfeeding continuity in women with COVID-19. Further research is needed to explore the long-term effects of different counseling approaches on breastfeeding outcomes during crises. Trial registration The study was registered on the Iranian Registry of Clinical Trials website on 29/06/2021 with the registration code IRCT20150731023423N19. It can be accessed via this link: https://irct.behdasht.gov.ir/user/trial/55391/view .